2021
DOI: 10.1261/rna.078696.121
|View full text |Cite
|
Sign up to set email alerts
|

The stem cell–specific protein TRIM71 inhibits maturation and activity of the prodifferentiation miRNA let-7 via two independent molecular mechanisms

Abstract: The stem cell–specific RNA-binding protein TRIM71/LIN-41 was the first identified target of the prodifferentiation and tumor suppressor miRNA let-7. TRIM71 has essential functions in embryonic development and a proposed oncogenic role in several cancer types, such as hepatocellular carcinoma. Here, we show that TRIM71 regulates let-7 expression and activity via two independent mechanisms. On the one hand, TRIM71 enhances pre-let-7 degradation through its direct interaction with LIN28 and TUT4, thereby inhibiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Ago2 is one of the Argonaute proteins that interact with microRNAs, forming a miRNA-induced silencing complex (miRISC), stem cells (mESCs). 19,31,32 Here, we found that knockdown of circ_0007429 increased Ago2 expression at the protein, but not at the mRNA, level; this effect was counteracted by overexpression of TRIM71 in addition to circ_0007429 knockdown. We found that knockdown or overexpression of TRIM71 alone affected Ago2…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Ago2 is one of the Argonaute proteins that interact with microRNAs, forming a miRNA-induced silencing complex (miRISC), stem cells (mESCs). 19,31,32 Here, we found that knockdown of circ_0007429 increased Ago2 expression at the protein, but not at the mRNA, level; this effect was counteracted by overexpression of TRIM71 in addition to circ_0007429 knockdown. We found that knockdown or overexpression of TRIM71 alone affected Ago2…”
Section: Discussionmentioning
confidence: 63%
“…Ago2 is one of the Argonaute proteins that interact with microRNAs, forming a miRNA‐induced silencing complex (miRISC), to repress posttranscriptional target gene expression. TRIM71 inhibits Ago2 production during self‐renewal of mouse embryonic stem cells (mESCs) 19,31,32 . Here, we found that knockdown of circ_0007429 increased Ago2 expression at the protein, but not at the mRNA, level; this effect was counteracted by overexpression of TRIM71 in addition to circ_0007429 knockdown.…”
Section: Discussionmentioning
confidence: 92%
“…The TRIM71 protein promotes stem cell proliferation and is strongly downregulated during exit from pluripotency [ 42 , 43 , 44 ]. We measured TRIM71 levels following miR-99a-5p mimic transfections at an early and late timepoint post hiPSC differentiation start.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation is carried out in different ways and outcomes in the suppression or enhancement of miRNA repressive functions. Through interaction with Ago, the proteins NHL-2 and Trim32 of nematode and human, respectively, [78,82] enhance miRNA-mediated gene regulation, while murine Trim71 suppresses it [79][80][81]83,84] ; Drosophila Mei-P26 both suppresses and activates, depending on the cellular environment. [85,86] TRIM-HNL proteins do not regulate the functioning of all miRNAs, but only particular ones; for some cases, this proved to be highly conserved let-7, [78,79,82,84,87] whose biological role is largely related to the change of cell programs during stem cell differentiation.…”
Section: E3 Ligases Of the Trim-nhl Family Regulate Mirna-mediated Ge...mentioning
confidence: 99%
“…Through interaction with Ago, the proteins NHL-2 and Trim32 of nematode and human, respectively, [78,82] enhance miRNA-mediated gene regulation, while murine Trim71 suppresses it [79][80][81]83,84] ; Drosophila Mei-P26 both suppresses and activates, depending on the cellular environment. [85,86] TRIM-HNL proteins do not regulate the functioning of all miRNAs, but only particular ones; for some cases, this proved to be highly conserved let-7, [78,79,82,84,87] whose biological role is largely related to the change of cell programs during stem cell differentiation. [22,88] It is important to note that TRIM-NHL-dependent regulation, despite the presence of a RING domain in the protein, generally is not associated with the ubiquitylation of Ago or other proteins: the ubiquitin ligase property of NHL-2 and Trim32 is not required for miRISC activation [78,82] ,…”
Section: E3 Ligases Of the Trim-nhl Family Regulate Mirna-mediated Ge...mentioning
confidence: 99%